Intercondylar Roof Impingement After Anatomic Double-Bundle Anterior Cruciate Ligament Reconstruction in Patients With Knee Hyperextension. (December 2013) - Matsubara, Hirokazu; Okazaki, Ken; Tashiro, Yasutaka; Toyoda, Kazutaka; Uemura, Munenori; Hashizume, Makoto; Iwamoto, Yukihide
Background: Although an anatomically placed graft in anterior cruciate ligament (ACL) reconstruction is reported to have a low risk of roof impingement, which may cause deterioration of the graft or an extension deficit, the incidence of roof impingement by these grafts has not been evaluated in hyperextensible knees. Purpose: To evaluate the incidence of roof impingement by the native ACL in hyperextensible knees and to examine the risk of roof impingement by anatomic placement of the ACL graft in hyperextensible knees. Study Design: Controlled laboratory study. Methods: Twelve patients were selected for a hyperextensible knee group (group A), defined as having hyperextension of the knee of greater than 10°. Twelve patients were recruited to a normal extension knee group (group B) with normal extension of the knee of less than 5° of hyperextension. Magnetic resonance imaging (MRI) scans of the knee positioned in 30° of flexion and full extension were acquired from all patients. The shape of the native ACL at full extension was compared between the groups. A 3-dimensional (3D) bone model was created from the acquired 2D MRI scans. A virtual anatomic double-bundle ACL reconstruction in each patient and a virtual anatomic single-bundle reconstruction in the patients in group A were performed using the 3D MRI bone models. The volume of the overlap between the graft and roof was calculated to evaluate graft impingement in each instance. Results: The MRI scans showed posterior bowing of the native ACL in the group A knees. The simulated double-bundle ACL reconstruction showed that the overlapped volume was significantly greater in patients in group A than in patients in group B ( P < .05). However, the overlap of the simulated single-bundle ACL reconstruction was significantly less than for the double-bundle ACL reconstruction ( P < .05). Conclusion: To reduce the risk of roof impingement by the graft, single-bundle ACL reconstruction with the graft placed at the center of the footprint might be the better method for patients with a hyperextensible knee than an anatomic double-bundle ACL reconstruction. Clinical Relevance: It is recommended that surgeons cautiously consider roof impingement after anatomic double-bundle ACL reconstruction in patients with a hyperextensible knee.